1994
DOI: 10.1300/j061v01n01_01
|View full text |Cite
|
Sign up to set email alerts
|

Restaurant and Foodservice Marketing

Abstract: The operating environment of today's restaurant and foodsenice industry is volatile, uncertain and complex (DeNoble and Olsen, Sirnon Crawford-Welch,PhD, is Assistant Professor of Hospitality Marketing and Research at the University of Nevada, Las Vegas; Director of Marketing and R e search for LEXES Leisure Group, Inc., a company specializ'mg in fmancing and marketing resort projects worldwide; and, Editor of this joumal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…40 It is reported that benefits predict behaviour better than personality and lifestyle, volumetric, demographic or geographic measures, which merely describe behaviour without explaining it. 41 A review of previous segmentation studies clearly demonstrates that there are distinct customer groups within the aggregate market. Managers can enhance sales volume and profits by developing market-specific strategies.…”
Section: Market Segmentationmentioning
confidence: 99%
“…40 It is reported that benefits predict behaviour better than personality and lifestyle, volumetric, demographic or geographic measures, which merely describe behaviour without explaining it. 41 A review of previous segmentation studies clearly demonstrates that there are distinct customer groups within the aggregate market. Managers can enhance sales volume and profits by developing market-specific strategies.…”
Section: Market Segmentationmentioning
confidence: 99%
“…The fast-food market has been used on other occasions to identify market segments based on benefits sought (Granzin and Olsen, 1997;Oh and Jeong, 1996). Crawford-Welch (1991) published an overview of market segmentation in hospitality, followed by an article focused primarily on segmentation for restaurants and foodservice operations (Crawford-Welch, 1994). The author points out the need to focus on segmentation variables other than the standard demographic variables used in most studies.…”
Section: 1mentioning
confidence: 99%
“…tle for market share. This overemphasis on price, as the sole means of attracting and retaining customers, however, may lead to the development of the "profitless prosperity syndrome" (Crawford-Welch, 1994), whereby restaurateurs can often sell their products but the price is not high enough to ensure adequate profit levels. As a consequence, the rate of business failure of restaurants is generally high (English, Josiam, Upchurch, & Willems, 1996), particularly in tourist resorts.…”
mentioning
confidence: 99%